Testing for Common Cyclical Features in Nonstationary Panel Data Models - Alain Hecq; Franz Palm; Jean-Pierre Urbain (Center for Economic Studies and ifo Institute (CESifo), 2000)
In this paper we extend the concept of serial correlation common features to panel data models. This analysis is motivated both by the need to develop a methodology to systematically stu dy and test for common structures and comovements in panel data with autocorrelation present and by an increase in efficiency coming from pooling procedures. We propose sequential testing procedures and study their properties in a small scale Monte Carlo analysis. Finally, we apply the framework to the well known permanent income hypothesis for 22 OECD countries, 1950-1992.
Keywords: 330; Panel data; serial correlation common features; permanent income